Pengaruh Sterilisasi Terhadap Angka Kuman Udara dan Risiko Infeksi Nosokomial di Ruang Operasi Rumah Sakit Nahdlatul Ulama Jombang - Betryana Agnes Pratiwi; Rusmiati Rusmiati; Setiawan Setiawan (FORIKES, 2020)
The results of examining the number of germs in the operating room of the Jombang Nahdlatul Ulama House have fulfilled the required requirements of 153 CFU/m3, 145 CFU/m3 and 85 CFU/m3. A high number of germs will provide a great risk for nosocomial infections. The purpose of this study was to study the sterilization instructions for airborne germ rates, with a sample size of 30. The results of this study produced airborne germ before and after the sterilization process, which were 78 CFU m3, 90 CFU/m3, 91 CFU/m3, 71 CFU/m3 and 74 CFU/m3, then after the sterilization process 63 CFU/m3 , 69 CFU/m3, 60 CFU/m3, 64 CFU/m3 and 64 CFU / m3. There was a decrease in numbers from day 1 to day 5 by 15 CFU / m3, 21 CFU/m3, 31 CFU/m3, 7 CFU/m3, 10 CFU/m3. The number of germs in the operating room both before and after did not meet the required quality requirements, but there was a reduction after sterilization. The different test showed a significant difference (α